The poems of W.B. Yeats. Volume two, 1890-1898 - Yeats, W. B. (William Butler), 1865-1939; McDonald, Peter, 1962- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
In this multi-volume edition, the poetry of W.B. Yeats (1865-1939) is presented in full, with newly-established texts and detailed, wide-ranging commentary. Yeats began to write verse in the nineteenth century, and over time his own arrangements of poems repeatedly revised and rearranged both texts and canon. This edition of Yeats's poetry presents all his verse, both published and unpublished, including a generous selection of textual variants from the many manuscript and printed sources. The edition also supplies the most extensive commentary on Yeats's poetry to date, explaining specific references, and setting poems in their contexts; it also gives an account of the vast range of both literary and historical influences at work on the verse. The poems are presented in order of composition, and major revisions or rewritings of poems result in separate inclusions (in chronological sequence) for these writings as they were subsequently reconceived by the poet. In this second volume, the poems of Yeats's early maturity emerge in the contexts of his engagement with Irish history and myth, along with nationalist politics; his increasing involvement with ritual magic and esoteric lore; and his turbulent, often unhappy, personal life. The poems of The Countess Kathleen and Various Legends and Lyrics (1892) reveal a poet of intense narrative power and metaphorical resource, adept at transforming miscellaneous sources into haunting and original poems. A major revision of his earlier narrative, The Wanderings of Oisin', takes place in this decade when Yeats is also taken up with the composition of elaborate and uncanny symbolic lyrics, many of them resulting from his love for Maud Gonne, that are finally collected in The Wind Among the Reeds (1899). This edition makes it possible to trace in detail Yeats's debts to folklore and magic, alongside his involved and often difficult private and public life, in poetry of exceptional complexity and power.
OCLC-licensed vendor bibliographic record.
Keywords: Ireland -- Poetry; English poetry -- 19th century; English poetry -- 20th century; LITERARY CRITICISM / General; LITERARY CRITICISM / Poetry